2019
DOI: 10.1128/mbio.02202-19
|View full text |Cite
|
Sign up to set email alerts
|

Population Genomics of GII.4 Noroviruses Reveal Complex Diversification and New Antigenic Sites Involved in the Emergence of Pandemic Strains

Abstract: GII.4 noroviruses are a major cause of acute gastroenteritis. Their dominance has been partially explained by the continuous emergence of antigenically distinct variants. To gain insights into the mechanisms of viral emergence and population dynamics of GII.4 noroviruses, we performed large-scale genomics, structural, and mutational analyses of the viral capsid protein (VP1). GII.4 noroviruses exhibited a periodic replacement of predominant variants with accumulation of amino acid substitutions. Genomic analys… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
80
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 67 publications
(88 citation statements)
references
References 65 publications
7
80
1
Order By: Relevance
“…In previous studies, it was shown that the current circulating GII.P16 variants exhibit amino acid changes in the polymerase. Five mutations were found in different studies: D173E; S293T; V332I; K357Q; and, T360A [ 8 , 11 , 18 ]. In this study, fourteen RdRp-sequences (234bp) were analyzed in the ORF1 region, amino acid changes S293T and V332I were found in all sequences ( Figure 5 ).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…In previous studies, it was shown that the current circulating GII.P16 variants exhibit amino acid changes in the polymerase. Five mutations were found in different studies: D173E; S293T; V332I; K357Q; and, T360A [ 8 , 11 , 18 ]. In this study, fourteen RdRp-sequences (234bp) were analyzed in the ORF1 region, amino acid changes S293T and V332I were found in all sequences ( Figure 5 ).…”
Section: Resultsmentioning
confidence: 99%
“…It has been shown for GII.4 viruses that amino acid changes in epitopes of the VP1 region resulted in global epidemics for decades. Antigenic drift variants of GII.4 persist for years until they are replaced by a new variant in a chronological sequential emergence [ 8 ], similar to influenza A viruses (reviewed by G.I. Parra [ 28 ]).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Norovirus presents multiple genotypes, but GII.4 strains are the predominant worldwide. GII.4 noroviruses have been shown the emergence of variants that present changes in antigenic sites, which facilitate escape from herd immunity elicited by previous variants (Debbink et al, 2012;Tohma et al, 2019).…”
Section: Introductionmentioning
confidence: 99%